Applying the Principles of the User Experience Questionnaire (UEQ) to the Design and Evaluation of Mobile Banking Applications that Support Persons with Disabilities - Aliyeva, Mujgan (ADA University, 2024)
When mobile banks have supported mobile phone technology, the sector of the financial services has undergone revolutionary transformations that now provide alternative options to the customers for their affairs related to personal finances. While this fast advance in the digital technology has the benefits, on the other hand, accessibility problems for those people who have disabilities, like dyslexia and color blindness have come into light. Under this research, a detailed analysis of how mobile banking applications for disadvantaged populations can be improved with UEQ ideas in aspect of its design and implementation is to be conducted in this thesis. More than a sizable number of world population is affected by dyslexia and the incapability in tint vision and this has negative effects on their operations with computer interfaces. A neurodevelopmental issue called dyslexia, which affects in reading comprehension and language processing, and abnormalities in photoreceptors in the retina that cause a color blindness, which may have an impact on the ability to differentiate colors, are the conditions that influence the visual processing system. Such surroundings pose a number of hurdles to digital access and, therefore, make it impossible for the individuals and communities affected by them to fully benefit from digitization and retain social and economic disparities. The study employs the UEQ framework (through which user experience is rated on the substantial aspects amongst which are ease of use, predictability, visual appeal, transparency, and excitement) with the aim of promoting inclusive designs. The goal is to generate a collection of design with heuristics in mind, that is helpful to dyslexic/colorblind users or take their issues into the account. This is a mixed research method that has got user research, usability testing and the iterative development of a mobile application prototype. The objective of this project will be to ameliorate the design codes by cognizant feedbacks from stakeholders and disabled people which will abide the resolutions of accessibility laid down by the recognized authorities. The supposition of this dissertation is the widening of the scope of inclusive design in the case of the digital interface, especially for the unprejudiced financial industry. Our work mainly is to improve the inclusivity of people with abilities in the digital economic domain, and in consequence, this would contribute to the fair and equitable society, by making the digital infrastructure an environment that is well accommodating and all encompassing. To begin with, this work takes a step towards the present product development design processes in the industry and also sets the standard of how the industry can move the future of all digital products forward when the main emphasis is placed on fun user experience and universal usability.
Keywords: Mobile banking -- Accessibility -- Design; User experience -- Disabilities -- Mobile applications; Dyslexia -- Technology accessibility; Color blindness -- Technology accessibility; Global population -- Disabilities; IT and Engineering